Optimization of the Ferromagnetic Nanoparticles Fabrication for Medical Applications - Wojtera, Katarzyna; Smolka, Krzysztof; Szymanski, Lukasz (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Carbon nanotubes possess remarkable properties, rendering them applicable across various fields, including medicine, particularly in hyperthermia treatments when filled with ferromagnetic material. This study focuses on refining the synthesis process of iron-filled multi-walled carbon nanotubes (Fe-MWCNTs) to produce high-purity nanocontainers with elevated iron content. Fe-MWCNTs were synthesized via catalytic chemical vapor deposition (CCVD), with temperature identified as a crucial determinant of synthesis efficiency. The paper also outlines the characterization of the resultant material. To gain insights into the underlying phenomena, computer simulations were conducted using COMSOL software.